2016
DOI: 10.1016/j.ijscr.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous infarction of fibroadenoma of breast—A case report with literature review

Abstract: HighlightsInfarction of breast fibroadenoma is a very rare complication.Spontaneous infarction occurs mostly during pregnancy or lactation.It poses a diagnostic dilemma of inflammatory diseases and inflammatory carcinoma due to their similarities both in clinical and cytological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Intratumoral hemorrhages of solid breast tumors have been reported in breast carcinomas and phyllodes tumors, more often in malignant than in benign phyllodes tumors, and is thought to be an effect of rapid tumor growth with hemorrhagic infarction or rupture of tumoral vessels . Conversely, spontaneous hemorrhage within a fibroadenoma, which is usually hemorrhagic infarction, is a very rare complication that occurs mostly during pregnancy or lactation …”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral hemorrhages of solid breast tumors have been reported in breast carcinomas and phyllodes tumors, more often in malignant than in benign phyllodes tumors, and is thought to be an effect of rapid tumor growth with hemorrhagic infarction or rupture of tumoral vessels . Conversely, spontaneous hemorrhage within a fibroadenoma, which is usually hemorrhagic infarction, is a very rare complication that occurs mostly during pregnancy or lactation …”
Section: Discussionmentioning
confidence: 99%
“…The definitive diagnosis of infarct fibroadenoma is the histopathological examination in which abundant areas of ischaemic necrosis, and hemorrhage with partial or null retention of the original architecture of the fibroadenoma without inflammatory or atypical cells can be observed [1]. In our case, the histological examination showed fibroadenoma with necrotic and hemorrhagic changes.…”
Section: Discussionmentioning
confidence: 62%
“…The most common recommended investigation for breast masses is FNAC [10]. In the FNAC, microscopic features of infarcted fibroadenoma are several individually scattered round or oval cells, without atypical features, and ghostly epithelial cells in a necrotic background [1]. In our case, the absence of suspicion of malignancy and the non-resolution of the condition after antibiotic treatment led us to perform tumor removal.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, ischemia/infarction-related factors may be involved in the SR of our patient's tumor. In addition, it has been reported that spontaneous infarction often occurs in benign breast lesions, including fibroadenoma, intraductal papilloma and lactating adenoma, and the most frequent clinical manifestation is a painful breast mass [16,17]. Our patient's painful breast tumor might have been due to infarction of the tumor, although the mechanism and trigger of the necrotic change were unclear.…”
Section: Discussionmentioning
confidence: 76%